Definition of Scientific Based Approaches to the Classification of Costs of Air Enterprise - Алі, Аль-газу (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
This article explores the main approaches to classification of expenses of aviation companies . The necessity of the improvement of the approaches for the purpose of distinguishing features for classification purposes of management and control of management has been proven. An author approach was suggested, which is based on management, accounting and economic control and analytical aspects of classification of operating costs of airlines.